DESCARTES AND FOUR CENTURIES OF EXACT SCIENCES - Kęstutis Masiulis (Problemos)
This article discusses Descartes’ input into the world picture of exact sciences of the Modern Age. The analytical geometry created by Descartes is considered to be the first successful attempt to develop analytical mathematics as a language of exact sciences. In the article, the author looks at Descartes’ rationalism and its impact on the development of modern sciences. The article analyses Descartes’ notions of inertia and the interrelation between matter and space.